(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article analyzes current hygienic aspects of working conditions in the construction industry in the context of technological transformation. The article examines both traditional harmful occupational factors and new risks associated with the introduction of robotics, additive technologies (3D printing of buildings), and digital control. Recommendations are offered for improving occupational disease prevention measures.